Wave simulation in the outer Río de la Plata estuary: evaluation of SWAN model - Dragani, Walter Cesar (2008)
This work discusses the implementation and validation of the SWAN model forced by NCEP/NCAR reanalyzed 10 m winds in the outer Río de la Plata (RDP) and adjacent continental shelf that will be used to study the wave climate in the region. Thirteen-month-long in situ data series of wave parameters are used to validate the results from numerical simulations. A set of numerical experiments is carried out in order to find a suitable computational domain to generate realistic simulations in the mouth of the RDP estuary. Numerical experiments including current and sea level fields are run, demonstrating that simulated wave parameters at the outer RDP are not significantly improved. A correction coefficient, dependent on wind speed, is applied to the wind drag factor in order to minimize the differences between simulated and observed wave parameters. The relatively low resolution wave model that satisfactorily simulates in situ wave heights and directions but slightly underestimates periods is a reliable tool for future applications and investigations.